Propriedades tecnológicas da madeira de Eucalyptus submetida a tratamentos de congelamento e termorretificação - Missio, André Luiz (2014)
This study aims to investigate chemical, physical, mechanical and surface properties of Eucalyptus grandis and Eucalyptus cloeziana wood subjected to different treatments of freezing and heat. To achieve this, six trees for each specie were used to prepare sample for each mechanical test. The samples were subjected to six thermal treatments. Freezing treatment was performed in a horizontal freezer at -22 ± 2°C for 72 hours, while heat treatment was performed using an oven with force air circulation at 180 and 200 ± 1°C for 3.5 hours. Sampling to perform chemical, physical and surface tests were obtained from samples used in mechanical characterization of wood. Chemical changes were evaluated quantitatively through wet process and qualitatively through infrared spectroscopy (ATR-IR). Physical properties evaluated were: weight loss, specific gravity, equilibrium moisture content, dimensional stability and hygroscopicity of wood. Mechanical evaluation was performed through static bending, impact strength, compression parallel to fibers and Janka hardness. Color and wettability of wood were evaluated using colorimetry and contact angle techniques, respectively. The main findings showed that freezing slightly affected the chemical properties of wood, in which the main changes were found in heat treatments, mainly at 200°C. Freezing improve in weight and equilibrium moisture content of wood, while heat treatment caused weight loss and decrease of equilibrium moisture content of wood. Both heat treatments improved dimensional stability of wood, however when freezing and heat was performed in a combination, they did not showed the best results. Regarding the hygroscopicity of wood, results obtained in heat treatment at 200°C should be highlighted. On the other hand, freezing treatment increased absorption of water. In general, freezing reduced mechanical properties of wood. Heat treatments increased stiffness at static bending and strength at compression parallel to fibers of wood however was responsible for reduction in other mechanical properties. Color of wood was affected mainly for heat treatments, in which a darkening of surface was observed and quantified by decrease of parameter L*. Wettability of wood slightly decreased after heat treatments. Influence of freezing on wettability of wood was related to the natural characteristic of wood from species studied because they did not showed a defined tendency. Therefore, it is believed that treatments performed in this study changed significantly the technological properties of wood.